2014
DOI: 10.1002/app.41286
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PLA/PEG/MWCNT electrospun nanofibrous scaffolds for anticancer drug delivery

Abstract: In the present study, polylactic acid (PLA)/polyethylene glycol (PEG)/multiwalled carbon nanotube (MWCNT) electrospun nanofibrous scaffolds were prepared via electrospinning process and their applications for the anticancer drug delivery system were investigated. A response surface methodology based on Box–Behnken design (BBD) was used to evaluate the effect of key parameters of electrospinning process including solution concentration, feeding rate, tip–collector distance (TCD) and applied voltage on the morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The important effect of the thickness of the PLA membrane on the release kinetics was shown. Furthermore, it was also shown that adding a water soluble polymer such as poly(ethylene glycol) (PEG) in the PLA matrix of the nanofibers enhanced the release of drug . In the same way, Xu et al showed that an increase of the hydrophilicity of nanofibrous membrane using a surfactant led to an increased drug release rate.…”
Section: Introductionmentioning
confidence: 99%
“…The important effect of the thickness of the PLA membrane on the release kinetics was shown. Furthermore, it was also shown that adding a water soluble polymer such as poly(ethylene glycol) (PEG) in the PLA matrix of the nanofibers enhanced the release of drug . In the same way, Xu et al showed that an increase of the hydrophilicity of nanofibrous membrane using a surfactant led to an increased drug release rate.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polyesters such as poly(lactic‐ co ‐glycolic acid), poly(ɛ‐caprolactone) (PCL), poly(lactic acid) (PLA), and poly(glycolic acid), are considered as most common synthetic polyesters used in bone tissue engineering and drug delivery . Among them, PLA has been widely utilized in bone regeneration applications because of its semicrystalline nature, good strength, low toxicity, and predictable biodegradation rate.…”
Section: Introductionmentioning
confidence: 99%
“…High porosity always results in poor compressive performances inevitably, while PABA-CFs reinforcement here can dominate the loss by their robust integration with polymer matrix. Generally, compressive strength for non-stress bone sites is required to be higher than 4 MPa [43]. The biocomposites containing 0.5 and 2 wt.% PABA-CFs can stand 4.36 and 5.48 MPa compressive strength, respectively (P < 0.05), which satisfies the basic mechanical requirements for non-stress bone tissue.…”
Section: Evaluations Of Cfs/pla-peg Biocompositesmentioning
confidence: 93%